Fuzzy Soft Skills Assessment through Active Learning Sessions - Novais, André Seixas de; Matelli, José Alexandre [UNESP]; Silva, Messias Borges [UNESP] (Elsevier, 2023)
This research aims to present a Fuzzy Expert System with psychologist expertise that seeks to assist professors, researchers and educational institutions in assessing the level of incorporation of students’ Soft Skills while attending Active Learning sessions. The difficulties encountered by higher education institutions, researchers and professors in evaluating subjective and behavioral components, such as Soft Skills, was one of the problems that motivated the undertaking of this research. The theoretical framework on which this work is based includes the development and evaluation of Soft Skills in students, some concepts and characteristics about Active Learning and the main attributes and properties of Fuzzy Logic. This research is of an exploratory applied nature, a qualitative and quantitative approach is proposed, in which the methodological triangulation between the bibliographic analysis, the case study and the modeling and implementation of the expert system called Fuzzy Soft Skills Assessment was used to achieve the objective proposed.
Keywords: Active Learning; Assessment; FSSA; Fuzzy; Soft Skills